HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DENGAN KECEPATAN LARI 40 METER SISWA KELAS V SDN 002 KOTO BARU KABUPATEN KUANTAN SINGINGI - Erlisnur Erlisnur; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract, Based on the observation that the author did in class V SDN 002 Koto Baru Regency Kuantan Singingi encountered symptoms or phenomena like, there are still many students who have not been able to run with optimal or not in accordance with the targets set. This is presumably due to lower limb muscle explosive power of students, so the authors wanted to do research on the relationship of explosive power leg muscle with running speed of 40 meters. This type of research is correlational study sample 27 students with a total sampling technique. Place of research conducted at SDN 002 Koto Baru while a study conducted in September-October 2016. The data in this study were obtained from the test results vertical jump and 40-meter test run. Normality test data using Liliefors with the results of normal distribution of data for both variables for calculating L <L table. After the data were analyzed using product moment correlation to student son rhitung = 0287 <rtabel 0553 for schoolgirl daughter rhitung = 0.001 <rtabel = 0532. Then it can be disimpulkam that "There was no relationship leg muscle explosive power with speed to run 40 meters fifth grade students of SDN 02 Koto Baru Regency Kuantan Singingi.Keywords: explosive power, muscular legs, running speed